Global health education in UK medical schools: a review of undergraduate university curricula - Matthews,NR; Davies,B; Ward,H (BMJ Global Health, 2020)
IntroductionIn recognition of our increasingly globalised world, global health is now arequired component of the medical school curriculum in the UK. We reviewthe current provision of global health education (GHE) in UK medical schoolsto identify gaps in compulsory teaching.MethodsWe conducted a review of the literature to inform a two-part electronic surveyof global health compulsory teaching, optional teaching and pre-electivetraining. Surveys were sent to all 33 UK medical schools for completion by thefaculty lead on global health and the nominated final year studentrepresentative.ResultsSurveys were returned by 29 (88%) medical school faculty and 15 (45%)medical student representatives; 24 (83%) faculty and 10 (67%) studentsreported including GHE in the core curriculum, however, there was widevariation in learning outcomes covered. On average 75% of faculty and 82%of students reported covering recommended global health themes ‘Globalburden of disease’, ‘Socioeconomic and environmental determinants ofhealth’, Human rights and ethics’, and ‘Cultural diversity and health’, whilstonly 48% of faculty and 33% of students reported teaching on ‘Healthsystems’ and ‘Global health governance’. Almost all institutions offeredoptional global health programmes and most offered some form of preelective training, although content and delivery were variable.ConclusionOver the last decade, the inclusion of global health in the core curriculum ofUK medical schools has increased dramatically. Yet, despite interest amongststudents, significant gaps are apparent in current GHE. Governing bodies inmedical education should establish a comprehensive national strategy to helpimprove access to fundamental GHE for all medical students.